2004
DOI: 10.1038/sj.embor.7400147
|View full text |Cite
|
Sign up to set email alerts
|

Functional conservation of interactions between a homeodomain cofactor and a mammalian FTZ‐F1 homologue

Abstract: Nuclear receptors are master regulators of metazoan gene expression with crucial roles during development and in adult physiology. Fushi tarazu factor 1 (FTZ-F1) subfamily members are ancient orphan receptors with homologues from Drosophila to human that regulate diverse gene expression programs important for developmental processes, reproduction and cholesterol homeostasis in an apparently ligand-independent manner. Thus, developmental and tissue-specific cofactors may be particularly important in modulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 25 publications
7
66
0
1
Order By: Relevance
“…Despite its vital functions in the development of many organs and tissues and the fact that it possesses a putative homeoprospero DBD at the C-terminus, Prox1 has not been shown convincingly to bind directly to target gene DNA. Instead, previous work by others and our group has shown that Prox1 functions as a corepressor of nuclear receptor LRH-1 in the regulation of lipid catabolism-related genes [23,24]. In such a regulation mechanism, Prox1 associates with target gene promoter through binding to LRH-1, which in turn directly binds to specific binding sites on the promoter.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Despite its vital functions in the development of many organs and tissues and the fact that it possesses a putative homeoprospero DBD at the C-terminus, Prox1 has not been shown convincingly to bind directly to target gene DNA. Instead, previous work by others and our group has shown that Prox1 functions as a corepressor of nuclear receptor LRH-1 in the regulation of lipid catabolism-related genes [23,24]. In such a regulation mechanism, Prox1 associates with target gene promoter through binding to LRH-1, which in turn directly binds to specific binding sites on the promoter.…”
Section: Discussionmentioning
confidence: 95%
“…However, our results showed that repression by PPARγ is not significantly affected when DCS and PCS are removed from the promoter (Figure 3), indicating that c-Jun-related mechanisms may not play a major part in PPARγ-dependent repression. On the Prox1 side, its corepressor activity on other target genes has been attributed to the repression domain ( Figure 5A), which has been reported to recruit histone deacetylase 3 (HDAC3) [24]. HDAC3 activity is related to negative epigenetic regulation of gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not known whether bile acids or drugs affect Prox1 interaction with FTF, HNF4␣, or PXR. Another recent report (28) shows that Prox1 interacts with FTF and inhibits SHP gene expression and that Prox1 specifically interacts with histone deacetylase (HDAC)3. HDACs are known to form complexes with nuclear receptors and corepressors and inhibit gene transcription (13).…”
Section: Discussionmentioning
confidence: 99%